Minor Construction Measures That Influences Vibration In Concrete Floors From Single And Dual Frequency Components - Sinin, Hamdan; Mohammad Nurul, Hoque; Norsuzailina, Mohamed Sutan (Inderscience Enterprises Ltd., 2015)
Concrete floor constructions often suffer from high frequency vibrations. Human’s aerobics works and various motors are sensitive to that kind of vibrations and it is of interest to find simple methods that reduce floor vibrations and thereby increase the comfort for habitants. Two steel framed concrete floor equipped with a vibration damping compound is used as test object under laboratory conditions. This paper covers three different studies with respect of human perception of vertical vibrations. The amplitudes and frequencies throughout the experiments are set to match those that might occur in concrete floor construction. Two concrete floors (1) Profiled Steel Sheet Concrete Floor (PCF) and (2) composite Concrete Floor (CCF) are taking as a test object. A generator generates signal from 30 to 60 Hz and the test subjects receive the vibrations sitting on the tested floor. In study number one, the values from sinusoidal signals are determined. In study number two, the values are determined in the presence of a base component. The third study is about annoyance from dual sinusoidal vibrations, always including a base signal at fixed amplitude. In similarity with study two, test person reported to be more annoyed as the second signal component gets close to the base frequency and naturally they also got more annoyed as the amplitude increased.